Waste Management in Ancient Times and Today from the Perspective of Teachers: Reflections to Diaries - Avcı, Dilek Erduran; Çeliker, Huriye Deniş (European Journal of Economics and Business Studies, 2021)
Wastes, which are results of human activities, have reached to amounts that threaten the lives of current and future human generations. The only way to create a waste-aware and recycling-aware society is through the education of our children. At this point, science teachers have a key role in formation of recycling generation. With this fact in mind, Project "Look forward, recycle: Recycler teacher" was conducted to make teachers witness the effects of two lifestyles, with and without wastes, to increase their knowledge on the issue, and to develop positive behavior about recycling. This project was conducted with the support of Scientific and Technological Research Council of Turkey and Mehmet Akif Ersoy University in Burdur during August, 2014. Twenty teachers from different provinces of Turkey participated in the project activities. Nature trainings included 23 activities and they were conducted by academic consultancy. In this process, participant teachers wrote diaries about the assigned subjects after completing their daily activities. Diary topics were determined in such a way that the participants could convey their feelings and opinions about the daily activity content. This study covers the results of five activity events and written diaries about them since the activity topics and contents were comprehensive. The names of these five events are as follows: (1) Let us trace the wastes, (2) Where to our wastes travel?, (3) Irregular and regular storage, (4) A journey in history: Introduction to the ancient city of Kibyra, and (5) Waste and waste management in ancient times. Teachers wrote diaries about the subject "Can you compare waste and waste management between ancient times and today?” after completing five events. The analysis of the diaries indicated that almost all teachers displayed an increased awareness and knowledge about waste and recycling increased by means of activities performed in modern technological facilities (purifying, waste collection facilities, wild-landfill storage areas) and historical remains. However, many teachers stated that still standing sewerage system made up of soil and stone of Kibyra ancient city and solid waste landfill site called as Bothros interested them much more rather than the modern technological system. Obviously teachers found waste management of ancient times much nature-friendly in comparison to the modern era.`